2019
DOI: 10.3390/su11061734
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Degrowth. Lessons from the 2008 Financial Crisis in Latvia and Iceland

Abstract: This paper investigates the role of governance dimensions in socio-economic transitions in line with degrowth, i.e., an equitable downscaling of the economy. Our focus is on experiences from the 2008 economic crisis in Latvia and Iceland. Although these cases are not in themselves examples of degrowth, we see them as important sources of empirical learning from major socio-economical transitions; furthermore, we see crises as possible starting points for future degrowth transitions. This paper applies a govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Earlier studies on the relation between crisis recovery and environmental impact stress the relevance of collaboration [28,29] and public awareness [30,31]. The many position papers on the topic of green recovery (we had little trouble identifying 105 of them) signal a growing awareness of sustainability issues.…”
Section: Knowledge Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on the relation between crisis recovery and environmental impact stress the relevance of collaboration [28,29] and public awareness [30,31]. The many position papers on the topic of green recovery (we had little trouble identifying 105 of them) signal a growing awareness of sustainability issues.…”
Section: Knowledge Contributionmentioning
confidence: 99%
“…Several sources note this finding based on past crises. For example, a case study comparing Latvia and Iceland [28] found that differences in political collaboration can be used to explain differences in the courses of sustainability transition attempts. Political collaboration refers both to coordination between public institutions and between the public and the government.…”
Section: Introductionmentioning
confidence: 99%
“…This can also happen through means that are unsustainable (Schneider et al, 2010), e.g. in an economic recession or a global crisis like the financial crisis in 2008 (Nyblom et al, 2019) or the COVID-19 pandemic (Barlow et al, 2020). Rather, degrowth should enable a "prosperous way down" (Mart ınez-Alier et al, 2010, p. 1741) by focusing on well-being, ecological sustainability, and social equity (Schneider et al, 2010).…”
Section: Emergence Of the Degrowth Paradigmmentioning
confidence: 99%
“…This can be illustrated by the Ukrainian conflict and the annexation of the Crimea Peninsula by Russia, promoting not only a redefinition of borders, but also the Euro‐Atlantic spatial order, marking the end of strategic partnerships of NATO with Turkey and the “reset” policies put forward by the ex‐ American President, Barack Obama, (Dale, ; Holmes, ; Martins, ; Schutt, ). This has also led to the EU economic and financial crisis (Buti & Carnot, ; Emontspool & Servais, ; Jozsef & Pal, ; Martins, ; Mikail, ; Nyblom, Isaksson, Sanctuary, Fransolet, & Stigson, ; Sánchez‐Zamora & Gallardo‐Cobos, ), the growing phenomenon of terrorism in European territory, not only on its spreading of fear and insecurity in populations, but also catalysing the resurgence of nationalist extremist groups, allied with the dangerous ascendance of the sense of belonging, preservation of culture and the notion of Nation (it should not be forgotten that in less than a century, similar movements, policies, and ideologies led to the World Wars). The recent disposition to estrangement between the UK and the EU (the Brexit ); or even the orthodox electoral results of economic strongholds, such as the United States of America, all seem to participate in the disintegration of the European Continent, and with it EU itself, long established before that as the CEE, but set in what was thought as solid as stone by the Maastricht treaty in 1992 (Treaty on European Union, ).…”
Section: Introductionmentioning
confidence: 99%